Dissolution and passivation mechanisms of chalcopyrite during bioleaching: DFT calculation, XPS and electrochemistry analysis. (November 2016) - Wang, Jun; Gan, Xiaowen; Zhao, Hongbo; Hu, Minghao; Li, Kaiyun; Qin, Wenqing; Qiu, Guanzhou
Graphical abstract: Highlights: DFT calculation and XPS verified the surface reconstruction of chalcopyrite. S2 2− and Sn 2− formed due to the surface reconstruction of chalcopyrite. The chemical formula of chalcopyrite should be Cu + Fe 3  + (S 2− )2 . Dissolution and passivation mechanisms of chalcopyrite bioleaching were discussed. Abstract: In this work, density functional theory (DFT) calculation, X-ray photoelectron spectroscopy (XPS) and electrochemistry analysis were carried out to investigate the dissolution process and passivation mechanisms of chalcopyrite in the presence of sulfur and iron oxidizing microorganisms. Both DFT calculation and XPS analysis indicated that the formula of chalcopyrite should be Cu + Fe 3  + (S 2− )2 . Disulfide (S2 2− ) and polysulfide (Sn 2− ) can be easily formed on the surface of chalcopyrite due to the surface reconstruction. The dissolution process of chalcopyrite in bioleaching was mainly dependent on redox potential. Chalcopyrite was predominantly directly oxidized to polysulfide when redox potential was lower than about 350 mV vs. Ag/AgCl and resulted in low dissolution rate. When redox potential was in the range of about 350–480 mV vs. Ag/AgCl, chalcopyrite was mainly transformed to intermediate species of Cu2 S rather than polysulfide, thus resulting in high dissolution rate. When redox potential was higher than about 480 mV vs. Ag/AgCl, chalcopyrite was principally directly oxidized to polysulfide which caused the passivation of chalcopyrite. Finally, a model of dissolution and passivation mechanisms of chalcopyrite in the presence of sulfur and iron oxidizing microorganisms was provided.